Effect of the soft segment on the fatigue behavior of segmented polyurethanes - Jimenez, Guillermo (2000)
Effect of the soft-segment structure and molecular weight on the microphase separation in segmented polyurethanes (SPU) was determined by means of differential scanning calorimetry, small-angle X-ray scattering, dielectric constant measurement, pulsed nuclear magnetic resonance, and thermoluminescence. Possible changes in the structural properties of SPU after cyclic mechanical fatigue were monitored using the same techniques as described above. Samples were divided in two series according to their soft-segment structure, i.e., one is linear poly(tetramethylene glycol) (PTMG), and another one with a methyl group on the PTMG chain. Hard segment consisted of 4,4'-diphenylmethane diisocyanate (MDI), and 1,4-butanediol (BD) as chain extender in both sets. It was found that phase separation increased for both types of SPU as the soft-segment molecular weight increased. Samples with methyl group showed little soft-segment crystallization. Upon fatigue, samples with a methyl group demonstrated a better fatigue resistance. 7 2000 Elsevier Science Ltd. All rights reserved.